2021
DOI: 10.1016/j.elerap.2021.101079
|View full text |Cite
|
Sign up to set email alerts
|

Risk-return modelling in the p2p lending market: Trends, gaps, recommendations and future directions

Abstract: The proposal for new financial products has been accompanied by new tools for risk management and profit in the Peer-to-Peer (P2P) lending market, one market in evolution, as an alternative for traditional investment and financing. For understanding this development, a systematic literature review and a bibliometric analysis of 104 papers published in the Web of Science database in the last decade are carried out using Scimat software. Our aim is to identify methodological elements, modelling components, analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 111 publications
0
14
0
1
Order By: Relevance
“…In contrast to this study, which took data from scientific publications from Scopus indexed journals. The results of the bibliometric analysis by Ariza-Garzón et al. (2021) conclude that several business problems in peer-to-peer lending have not been explored in previous literature, especially those related to fraud, debt collection, credit provision (LGD), third-party collateral warranties, etc.…”
Section: Literature Reviewmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to this study, which took data from scientific publications from Scopus indexed journals. The results of the bibliometric analysis by Ariza-Garzón et al. (2021) conclude that several business problems in peer-to-peer lending have not been explored in previous literature, especially those related to fraud, debt collection, credit provision (LGD), third-party collateral warranties, etc.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Previously, there have been several studies conducting bibliometric studies in related fields. Ariza-Garzón et al. (2021) in their study identified the most influential scientific publications and study developments in the field of peer-to-peer lending using bibliometric analysis techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Identify borrowers' credit risk is one of the key concerns of the credit industry (Ariza-Garzon et al, 2021;Crook et al, 2007). Numerous studies have been conducted on the models used in credit scoring to identify the credit risk of borrowers more efficiently.…”
Section: Credit Scoringmentioning
confidence: 99%
“…Providing digital credit services and issuing its products through the Internet channel has made them more convenient for Internet platforms, third-party financial institutions, as well as borrowers (Francis et al, 2017). Particularly, it expands the range of applications for credit scoring, allowing for the identification of borrowers' credit risk with more useful information (Ariza-Garzon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%